ChemInform Abstract: The Significance of Acid/Base Properties in Drug Discovery. Issue 20 (25th April 2013) - Manallack, David T.; Prankerd, Richard J.; Yuriev, Elizabeth; Oprea, Tudor I.; Chalmers, David K.
Abstract Review: 62 refs.